Incidente of microbial contaminants in sugarcane micropropagation - Yelenys Alvarado-Capó; Nayanci Portal González; Leyanis García-Aguila; Daimí Ramírez; Yudith Gutiérrez (Biotecnología Vegetal, 2003)
The incidence of microbial contaminants in Establishment, Multiplication and Rooting stages of the sugarcane micropropagation was determined by visual observation of the culture vessels. The type of microorganism was confirmed in observations to the optic microscope. The percentage of contamination for microbial group was determined in 731 apexes in the Establishment stage, in each multiplication subculture (up to the seventh) in a total of 5 225 in vitro plants and 6 650 in the Rooting stage. In three stages the presence of microbial contaminants was verified (filamentous fungi, bacteria and yeasts) with prevalence of the bacteria (13.7-31.6%). In the Multiplication stage the percentages of bacterial contamination were increased with the number of subcultures. The results indicated the high incidence of microbial contaminants in sugarcane micropropagation and the necessity of paying attention to the control of the bacterial contamination.